PENGARUH FAKTOR MODAL PSIKOLOGIS, KARAKTERISTIK ENTREPRENEUR, INOVASI, MANAJEMEN SUMBER DAYA MANUSIA, DAN KARAKTERISTIK UKM TERHADAP PERKEMBANGAN USAHA PEDAGANG DI PASAR TRADISIONAL (Studi kasus pada Pedagang Sembako dan Snack di Pasar Peterongan) - Reni Shinta Dewi (Jurnal Administrasi Bisnis, 2013)
This research intends to find out the effect of psychological capital entrepreneur, human resource management, innovation, characteristics of the entrepreneur, and SMEs characteristics to the development of businesses. The study was conducted in Semarang city, the sample were 32 merchants who employ labor at Peterongan market. The research type is explanatory research. Data analysis using linear regression. The results showed that Psychological Capital Variables, Entrepreneur Characteristics, Innovation, Human Resource Management and Characteristics Of SMEs either partially or simultaneously have an influence on the Development Of Business In Traditional Markets of Peterongan. Psychological Capital is the most influencing variable to the Development Of Business. Recommendation for trader in the traditional market is they need to always foster an optimistic attitude in running the business. This attitude can be formed by creating a bevy of fellow traders so that every issue can be resolved soon. Besides the characteristic form of motivation to strive entrepreneur must be maintained by attending various training such as retail training in financial management, merchandise arrangements that will grow the innovation and creativity that never died for business development.